A democratização racial na universidade : a legitimidade e os limites das ações afirmativas no acesso ao ensino superior - Pereira Júnior, Altemar Constante (Universidade do Vale do Rio dos Sinos, 2010)
The present study discusses the possibility of adopting affirmative action policies as a way to promote inclusion and racial democratization in Brazilian's universities. From the experience of the United States, where there is more than fifty years has been developed such policies, seeks to draw a parallel between the effectiveness of affirmative action in north america and how the programs have been developed to include the black population on the banks of Brazilian universities. Considering that Brazil is a signatory to the World Conference Again st Racism, Racial Discrimination, Xenophobia and Related Intolerances, held in 2001, and since then undertakes to adopt measures to promote diversity, the study shows how the major federal universities are organized to develop their forms of affirmative action, represented by quotas to the entrance exam. In this perspective, the research is developed with theoretical reference by John Rawals's lesson, especially in its presentation of the principle of difference, and the positioning of Ronald Dworkin about affirmative action. On the other hand, the research defends the reasons that legitimate affirmative action just about terms of access of black people in institutions of higher education, shouldn't such a policy be deployed in other democratic contest, failing to confront the constitutional principle of equality.
Keywords: Ação afirmativa; Universidade; População negra; Meritocracia; Affirmative action; College; Black population; Meritocracy; ACCNPQ::Ciências Sociais Aplicadas::Direito